ANALISIS RANTAI NILAI CABAI RAWIT KABUPATEN LOMBOK TIMUR, PROVINSI NUSA TENGGARA BARAT PASCA PANDEMI COVID-19 - Renaldi, Eddy; Nugraha, Adi; Pardian, Pandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Cayenne pepper is a horticultural commodity that affects the inflation rate. This study aims to determine the value chain and value added to chili commodities in East Lombok Regency, West Nusa Tenggara Province, so that potential increases and value distribution in the cayenne pepper marketing chain can be mapped. Primary data was obtained through semi-structured interviews conducted with actors involved in the cayenne pepper supply chain, which were traced using the Rapid Market Appraisal technique. Value chain analysis is performed to calculate added value at each level of supply chain actors. The results of the analysis show that in general there are 4 lines in the supply chain for cayenne pepper before it reaches the final consumer, namely farmers, collectors, wholesalers and retailers. In this chain, farmers gain the largest proportion of added value compared to other actors.